Impact of seed system interventions on nutrition in low- and middle-income countries: A scoping review - Nabuuma, Deborah Sandra; Reimers, Christine; Hoang, Ky The (2024)
The scoping review was aimed at mapping available evidence on seed systems interventions and the enabling and inhibiting environment within which they may or may not improve nutrition outcomes. A protocol was developed in accordance with the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) and the methodology of the Joanna Briggs Institute (JBI) Reviewer’s Manual for scoping reviews, to identify studies on seed system interventions in low- and middle-income countries that included nutrition and food security outcomes. PubMed, Web of Science and AGRIS electronic databases were searched. 7555 studies were identified and after removal of duplicates, 6860 studies were screened based on a predefined population, concept and context criteria. 84 studies were eligible for charting, during which 40 studies were excluded and 3 were identified for inclusion. This resulted in 41 studies that were analysed. Data for the 41 studies is presented in this dataset.